2014
DOI: 10.1021/bc400396z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluorophore-Tagged Xylosides That Prime Glycosaminoglycan Chains

Abstract: Biosynthesis and functions of glycosaminoglycan (GAG) chains are complex and remain elusive. To better understand the factors that regulate the biosynthesis and functions, fluorophore-tagged xylosides carrying two different linkages between fluorophore and xylose residue were synthesized and evaluated for their ability to prime GAG chains such as heparan sulfate (HS), chondroitin sulfate (CS), and dermatan sulfate (DS) in various cell lines. These in vitro studies resulted in the identification of fluorophore-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…21,32,33,35 For example, we have earlier investigated a series of hydroxynaphthyl 1-thio-β-D-xylopyranosides that all showed strong priming of relatively short GAG chains. 33,35,37 Kuberan and co-workers 27,28,34,[38][39][40] have made several series of amideand triazole-linked xylosides of which the GAG priming ability varied with variations in the aglycon moiety. 33,35,37 Kuberan and co-workers 27,28,34,[38][39][40] have made several series of amideand triazole-linked xylosides of which the GAG priming ability varied with variations in the aglycon moiety.…”
Section: Part B: Variation At the Anomeric Center Or Of Absolute Confmentioning
confidence: 99%
See 1 more Smart Citation
“…21,32,33,35 For example, we have earlier investigated a series of hydroxynaphthyl 1-thio-β-D-xylopyranosides that all showed strong priming of relatively short GAG chains. 33,35,37 Kuberan and co-workers 27,28,34,[38][39][40] have made several series of amideand triazole-linked xylosides of which the GAG priming ability varied with variations in the aglycon moiety. 33,35,37 Kuberan and co-workers 27,28,34,[38][39][40] have made several series of amideand triazole-linked xylosides of which the GAG priming ability varied with variations in the aglycon moiety.…”
Section: Part B: Variation At the Anomeric Center Or Of Absolute Confmentioning
confidence: 99%
“…28 Recently, we made a systematic investigation of the effects of the xylose-aglycon distance on GAG priming ability. It has also been reported that a triazole-linker, compound 58, increased the GAG priming compared to 59.…”
Section: Part C: Variation Of Linker Lengthmentioning
confidence: 99%
“…[61][62][84][85][86][87][88] Kuberan and co-workers have synthesized a large library of xylosides using click-chemistry, containing a triazole ring linked to the xylose residue. 69,72,[89][90] Naphthyl β-L-xylopyranoside does not prime GAG chains. 91 In order to study cellular effects, several Chinese hamster ovary (CHO) cell lines, with defect GAG biosynthesis have been developed: pgsA-745 cells lack the enzyme XylT2, pgsA-761 cells are defective in β4GalT7, and pgsI-208 cells are deficient in UXS1.…”
Section: Glycosaminoglycans and Proteoglycansmentioning
confidence: 99%
“…[61][62] Over the years, several hundred xylose derivatives have been synthesized and tested to explore cellular uptake, priming of GAG chains, and inhibition of biosynthetically important enzymes. Xylosides have been synthesized with variation in: the aglycon size and hydrophilicity, 57,[63][64][65][66][67][68][69][70] the distance between the carbohydrate and the aglycon, 63,69,[71][72] and the anomeric configuration. 57,[72][73][74][75][76][77][78] Furthermore, C-xylosides, 66,77,79 S-xylosides, 57, 63, 66, 76-77, 80 N-xylosides, 66 phosphorylated xylosides, 81 and peracylated xylosides [82][83] have been synthesized.…”
Section: Glycosaminoglycans and Proteoglycansmentioning
confidence: 99%
“…Western blots were conducted with monoclonal antibody CS56 (Sigma Aldrich) with goat antimouse IgM-HRP secondary (Fisher Scientific). Xylosides were synthesized, purified, and analyzed as previously described (Victor et al, 2009;Tsuzuki et al, 2010;Nguyen et al, 2013;Tran and Kuberan, 2014). All other reagents were acquired from Fisher Scientific or Sigma Aldrich.…”
Section: Reagentsmentioning
confidence: 99%